Penguatan Kemandirian Finansial Keluarga melalui UMKM bersama Ibu-Ibu PKK - Supriyanto, Didik; Rahmawati, Lilis; Patricia Firnanda, Michel (Universitas Pangeran Diponegoro Nganjuk, 2025)
This community service program addressed the challenge of limited economic opportunities for women in Ngujung Village by focusing on empowering PKK members through UMKM-based culinary activities. The primary objective was to enhance participants’ skills and knowledge in managing small businesses and fostering family financial independence. The approach combined case studies, identification of best practices, and hands-on training to equip participants with practical abilities in business opportunity recognition, basic financial management, and marketing strategies for UMKM products. The results demonstrated increased awareness among PKK members about the importance of financial autonomy, higher motivation to start or expand small businesses, and strengthened collaboration between the community service team, village authorities, and participants. Overall, the program positively impacted participants’ entrepreneurial skills, creativity, and engagement in local economic development, providing a foundation for sustainable empowerment initiatives.